Proses Padu Serasi Dalam Pengembangan Kawasan Pesisir Kota Semarang - Mohammad Agung Ridlo; Eppy Yuliani (Universitas Islam Sultan Agung Semarang, 2019)
ABSTRACTIn almost all regions of the Coastal Indonesia conflicts often occur with various interests. The main cause of this problem (conflict) is spatial planning that does not / does not pay attention to Coastal Resources in the region. This happens one of them as information that needs to be used. Various parties have an interest in their own goals, objectives and plans for exploiting the Coastal Resources. Likewise, the City of Semarang, in developing Coastal / Coastal areas, should ask permission from the holder of a fixed land right or at least leave a small amount of space from the front area of Semarang City as a public open space. Semarang City is a city that is very poor in public space. In the management of the Coastal area it is necessary to have direction in this Coastal area as a public space, not a free trade process with profit-oriented goals. But still giving access to the free space of the beach that can be entered by permitted. Free space can be realized by giving a certain free distance from the coastline. Therefore, the combination of spatial plans and zoning plans is needed. In the process of regional spatial planning (RTRW) and zoning plans (RZ) of Coastal areas, it is necessary to make a harmonious process.Key Words: Mix and Match, Development, Coastal Areas ABSTRAKKawasan pesisir menjadi kawasan yang mengalami berbagai permasalahan dari berbagai sudut kepentingan. Penataan ruang pada kawasan pesisir yang belum dapat selaras dengan potensi sumberdaya pesisir, menjadi salah satu alasan dari munculnya berbagai permasalahan yang ada. Tidak satupadunya tujuan, target dan rencana dalam pengelolaan sumberdaya pesisir membuat penataan kawasan pesisir kurang menyatu. Demikian pula halnya dengan Kota Semarang, dalam mengembangkan kawasan pesisir/pantai semestinya berwenang mengingatkan para pemegang izin/hak guna lahan untuk tetap menjadikan atau minimal menyisakan sedikit ruang dari kawasan terdepan (muka) Kota Semarang ini sebagai ruang terbuka publik. Kota Semarang merupakan kota yang sangat miskin akan ruang publik. Dalam pengelolaan kawasan pesisir perlu adanya pengarahan bahwa kawasan pesisir ini sebagai ruang publik, tidak sekedar suatu proses dagang semata dengan tujuan profit oriented. Namun tetap memberikan akses ke ruang bebas dari pantai yang dapat dimasuki oleh siapapun. Ruang bebas dapat diwujudkan dengan memberikan jarak bebas tertentu dari garis pantai. Oleh karenanya, maka perpaduan rencana tata ruang darat dan rencana zonasi pesisir sangat diperlukan. Dalam proses penyusunan rencana tata ruang wilayah (RTRW) dan rencana zonasi (RZ) wilayah pesisir, perlu dilakukan proses padu serasi.Kata Kunci: Padu Serasi, Pengembangan, Kawasan Pesisir